The Warped Product of Hamiltonian Spaces - Attarchi, H.; Rezaii, M.M. (Журнал математической физики, анализа, геометрии, 2014)
In this paper, the geometric properties of warped product Hamiltonian spaces are studied. It is shown there is a close geometrical relation between a warped product Hamiltonian space and its base Hamiltonian manifolds. For example, it is proved that for nonconstant warped function f, the Sasaki lifted metric G of Hamiltonian warped product space is bundle-like for its vertical foliation if and only if based Hamiltonian spaces are pseudo-Riemannian manifolds. Изучены геометрические свойства гамильтоновых пространств в виде искривленных произведений. Показано, что между гамильтоновым пространством - искривленным произведением и его базовыми гамильтоновыми многообразиями существует тесная геометрическая связь. Например, доказано, что для непостоянной искривляющей функции f метрика Сасаки G для гамильтонова пространства - искривленного произведения является расслоенной метрикой по отношению к ее вертикальному слоению тогда и только тогда, когда базовые гамильтоновы пространства являются псевдо-римановыми многообразиями. The first author would like to thank the INSF for the partially support on the grant number 92006616.